(untitled) (REVISTA AMBIENTAL AGUA, AIRE Y SUELO, 2015)
The in situ monitoring system for petroleum derivatives aims to easily detect where petroleum derivatives are being misused and how often. By identifying an affected area, preventive measures can be taken to improve not only the direct benefits but also the quality of life of others. The project, based on spectrometry, will demonstrate the intended approach, outline some basic steps, and aim to redesign a low-cost system with guaranteed results for the benefit of the community.